Understanding Medical Students’ Perceptions of Evolutionary Medicine and Evolution: A Cross-Sectional Analysis of Acceptance, Knowledge, and Barriers in Egypt - Mohamed Ibrahim Mohamed; Nada Ashraf Al-Shafey; Omar El-Kholy; Youssef ElSourady; Azza Baraka; Marwa Schumann (International Medical Education, 2026)
Evolutionary medicine (EM) applies evolutionary principles to explain disease mechanisms and improve clinical practice, yet it remains underrepresented in medical education, particularly in non-Western settings. This study investigated Egyptian medical students’ perceptions of EM by assessing their acceptance of evolutionary theory, knowledge of natural selection, and perceived barriers to EM education. A cross-sectional, multicentre online survey was conducted among 589 undergraduate medical students from seven Egyptian medical schools. Acceptance of evolution was measured using the Measure of Acceptance of the Theory of Evolution (MATE 2.0), and knowledge was assessed using the Conceptual Inventory of Natural Selection (CINS). Students demonstrated limited knowledge and relatively low acceptance of evolutionary theory, while a substantial proportion had no previous awareness of EM. Nevertheless, many students supported integrating EM into medical curricula and recognized its potential contribution to research and clinical practice. Curriculum overload and religious concerns were among the most frequently perceived barriers to EM integration. These findings identify important gaps in students’ exposure to and understanding of evolutionary concepts and support the integration of clinically relevant, culturally responsive evolutionary education into undergraduate medical curricula to strengthen evolutionary literacy and facilitate meaningful engagement with EM.